Urak Lawoi Languageon Bulon Island: Documenting and Characterizing a Near-Vanishing Language - Aksornjarung, Prachamon (วารสารปัญญาภิวัฒน์, 2013)
Abstract Urak Lawoi language is spoken by a group of minority people whose settlement scattering in different islands of the 6 southern provinces of Thailand-Phuket, Krabi, Pang-nga, Ranog, Trang and Satun. In 2005 only 4,200 people (middle-toold-aged) were reported still communicating through this generations-long spoken language. Importantly, the number of Urak Lawoi speakers tends to be decreasing due to the influence of different factors. A well-accepted fact concerning world languages is that any language having its own written form can hardly be in danger of extinction. In order to prevent this sea people’s language from vanishing, as has occurred to thousands of minority languages once existed in the World’s 5 continents, this study was conducted with the objective to: 1) search for and document the spoken words of the language into the written form using the International Phonetic Alphabets (IPA); 2) quantify the words actually spoken by the residents of Bulon Island; and 3) characterize words and phrase of the language. The language data were collected from a sample group consisting of thirty-eight informants-22 male and 16 female having elementary to degree education and those having no Thai literacy, residing on Bulon Island, in Satun Province of Thailand. Small group interviews using 1,200 picture and word cue cards, together with in-depth interviews were performed to collect data. Information of each lexical token was hand-written in Thai language orthography and cross checked twice for accuracy before transcribed using the IPA, followed by corresponding English meanings. Research results are as follow. We successfully found and recorded in writing with IPA symbols 759 Urak Lawoi words spoken by residents of Bulon Island. Urak Lawoi words and phrases share certain characteristics with Malay while borrowing a number of Thai words in coining new words. Compound words and phrases are head noun-fronted. Also found is that Urak Lawoi language lacks nuances, for colors, for instance. Keywords: Urak Lawoi minority language conservation, language vanishing, lexicon in International Phonetic Alphabets, Bulon Island. บทคัดย่อ ภาษาอูรักลาโว้ย เป็นภาษาที่ใช้พูดสื่อสารโดยชนกลุ่มน้อยกลุ่มหนึ่งที่ตั้งถิ่นฐานกระจัดกระจายอยู่ในเกาะต่างๆ ในภาคใต้ 6 จังหวัดของประเทศไทย ได้แก่ ภูเก็ต กระบี่ พังงา ระนอง ตรัง และสตูล เมื่อปี ค.ศ. 2005 ได้มีรายงานว่ามีผู้ที่ยังสื่อสารด้วยภาษาอูรักลาโว้ยซึ่งเป็นภาษาพูดที่เก่าแก่นับหลายชั่วอายุคนอยู่เพียง 4,200 คน (ซึ่งเป็นผู้ที่อยู่ในวัยกลางคนถึงวัยชรา) ที่สำคัญคือจำนวนผู้พูดภาษานี้ได้ลดลงอย่างต่อเนื่องอันสืบเนื่องจากอิทธิพลของปัจจัยต่างๆ ข้อเท็จจริงที่เป็นที่ยอมรับประการหนึ่งเกี่ยวกับภาษาของโลกคือภาษาใดๆ ที่มีภาษาเขียนจะมีความเป็นไปได้น้อยที่จะสูญสิ้นไป เพื่อป้องกันไม่ให้ภาษาของชาวเลกลุ่มนี้สูญหายไปเหมือนดังที่ได้เกิดขึ้นแล้วกับภาษาชนกลุ่มน้อยต่างๆ ที่เคยดำรงอยู่ในทวีปต่างๆ ทั้ง 5 ทวีป การศึกษาวิจัยนี้จึงมีจุดประสงค์เพื่อ (1) สืบค้นและบันทึกคำศัพท์ภาษาพูดของภาษาอูรักลาโว้ย บนเกาะบูโหลน ไว้เป็นลายลักษณ์อักษรด้วยสัญลักษณ์ทางสัทศาสตร์สากล (IPA) (2) ศึกษาจำนวนคำศัพท์ที่ชาวเกาะบูโหลนใช้พูดสื่อสารกัน และ (3) ศึกษาคุณลักษณะทางภาษาของคำศัพท์และวลี ข้อมูลทางภาษาในโครงการวิจัยนี้สืบค้นจากผู้ให้ข้อมูลชาวอูรักลาโว้ยที่อาศัยอยู่ที่หมู่เกาะบูโหลน จังหวัดสตูล จำนวน 38 คน เพศชาย 22 คน และเพศหญิง 16 คน มีระดับการศึกษาตั้งแต่ประถมศึกษาถึงปริญญาตรี และผู้ให้ข้อมูลที่ไม่รู้หนังสือไทยเก็บข้อมูลด้วยการสัมภาษณ์เชิงลึกกลุ่มย่อยประกอบการใช้บัตรภาพและบัตรคำ 1,200 บัตร ข้อมูลคำศัพท์ที่สืบค้นได้ถูกบันทึกด้วยมือเป็นภาษาไทย และตรวจสอบความถูกต้อง 2 ครั้งก่อนบันทึกด้วยสัญลักษณ์สัทศาสตร์สากลพร้อมคำแปลภาษาอังกฤษ ผลการวิจัยในการศึกษาครั้งนี้คือ ได้ค้นพบและบันทึกคำศัพท์ภาษาอูรักลาโว้ยด้วยสัญลักษณ์ทางสัทศาสตร์สากล จำนวน 759 คำ คำศัพท์และวลีภาษาอูรักลาโว้ยมีลักษณะบางประการเหมือนภาษามาลายู อีกทั้งยังพบว่าได้มีการยืมคำภาษาไทยประกอบการประดิษฐ์คำศัพท์ใหม่ในส่วนของลักษณะทางภาษาของคำศัพท์ พบว่าคำผสมและวลีในภาษาอูรักลาโว้ย ประกอบด้วยนามหลักอยู่ต้นคำตามด้วยส่วนขยาย นอกจากนี้ พบว่าภาษาอูรักลาโว้ยขาดคำเพื่ออธิบายความหลากหลายและละเอียดอ่อนทางความหมายของบางสิ่ง เช่น คำสำหรับอธิบายความแตกต่างของระดับของสีแต่ละสี เป็นต้น คำสำคัญ : ภาษาชนกลุ่มน้อยอูรักลาโว้ย การอนุรักษ์ภาษา การสูญหายของภาษา สัญญลักษณ์ทางสัทศาสตร์สากลเกาะบูโหลน